2005
DOI: 10.1038/sj.gene.6364235
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide search for sarcoidosis susceptibility genes in African Americans

Abstract: Sarcoidosis, a systemic granulomatous disease of unknown etiology, likely results from an environmental insult in a genetically susceptible host. In the US, African Americans are more commonly affected with sarcoidosis and suffer greater morbidity than Caucasians. We searched for sarcoidosis susceptibility loci by conducting a genome-wide, sib pair multipoint linkage analysis in 229 African-American families ascertained through two or more sibs with a history of sarcoidosis. Using the Haseman-Elston regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 49 publications
6
54
0
2
Order By: Relevance
“…More detailed descriptions of the study sample, recruitment methodology and genotyping can be found in previous publications. 3,19 Genotyping and model-free linkage analysis A fluorescence-based genotyping method was used to type the Weber 10 microsatellite marker set, which consists of 380 markers across 22 autosomes spaced an average of 9.18 cM apart. To investigate the genetic linkage of sarcoidosis phenotypes, we reanalyzed these genotype data from the SAGA study 3 using an affected relative pair multipoint genetic linkage analysis approach implemented in the program LODPAL of the S.A.G.E.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed descriptions of the study sample, recruitment methodology and genotyping can be found in previous publications. 3,19 Genotyping and model-free linkage analysis A fluorescence-based genotyping method was used to type the Weber 10 microsatellite marker set, which consists of 380 markers across 22 autosomes spaced an average of 9.18 cM apart. To investigate the genetic linkage of sarcoidosis phenotypes, we reanalyzed these genotype data from the SAGA study 3 using an affected relative pair multipoint genetic linkage analysis approach implemented in the program LODPAL of the S.A.G.E.…”
Section: Methodsmentioning
confidence: 99%
“…2 More recently, we reported from the sarcoidosis genetic analysis (SAGA) study, the first genome scan in African Americans, several regions of suggestive linkage to sarcoidosis susceptibility with the most prominent peak at D5S2500 on chromosome 5q11. 3 The disparity in results between the two genome scans and the phenotypic variability of sarcoidosis suggest that linkage analysis of specific sarcoidosis phenotypes may discover disease genes that analyses of sarcoidosis susceptibility alone have failed to detect.…”
Section: Introductionmentioning
confidence: 99%
“…Disease susceptibility and progression are thought to depend partly on genetic factors. [1][2][3][4] Of these genetic factors, only the human leukocyte antigen gene complex has been repeatedly confirmed to be associated with sarcoidosis in multiple populations of multiple ethnicity. Polymorphisms in a number of non-human leukocyte antigen genes have been reported to be associated with sarcoidosis, but so far confirmation has been difficult (recently reviewed by Grunewald 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, numerous attempts to define disease susceptibility genes, usually by candidate gene approaches, although more recently using haplotype analysis, have yielded results that are poorly reproducible [5]. More recently, two whole genome scans have yielded differing results, possibly because two different populations were studied [6,7]. Recent successful genetic analyses have relied on defining very clear phenotypes, such as Lofgren's syndrome, to demonstrate reproducibility between populations [8,9].…”
Section: Introductionmentioning
confidence: 99%